Pengaruh Disiplin Kerja dan Lingkungan Kerja yang Mempengaruhi Kinerja Karyawan di Pt. Xyz - Devry Nugraha (Syntax Literate, 2023)
The objectives of the research to be carried out are as follows: (a) To find out the work discipline and work environment at PT. XYZ. This research uses quantitative methods based on the philosophy of positivism used to study certain populations or sample groups, use research tools to collect data, analyze quantitative or statistical data, and test hypotheses that have been previously established. Results, Validity testing is used to measure the validity or invalidity of a questionnaire statement distributed to respondents, then the questionnaire is said to be valid if the questionnaire statement is able to reveal something that will be measured by the questionnaire. While reliability testing is a method for measuring a statement's answer, a questionnaire is said to be reliable if the answers to the statement are consistent. Measurement of validity and reliability in this study was carried out using SPSS 20 software tools. Conclusion, Work discipline at PT. XYZ is already doing well. However, there are still things that need to be improved regarding delays and work guidelines. Likewise with the work environment at PT. XYZ that runs well